The use of steroids to prevent cutaneous reactions to benznidazole in patients with Chagas disease. (1st April 2013) - Górgolas, Miguel; Robles, Ignacio; Cabello, Alfonso; Pérez-Tanoira, Ramón; Peremarch, Concepción Pérez-Jorge; Fernández-Roblas, Ricardo; Williams, Frances; Rincón, José Manuel Ramos
<x xml:space="preserve">Abstract</x> The treatment of Chagas disease is limited by the frequent cutaneous side effects of benznidazole. We tested the use of steroids plus escalating doses of benznidazole to prevent this complication in 17 adult patients with chronic Trypanosoma cruzi infection and found extremely good tolerance. A randomized trial is warranted.